2020
DOI: 10.3390/rs12010130
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Different Mapping Functions and Gradient Models in the Determination of Slant Tropospheric Delay

Abstract: Global navigation satellite systems (GNSSs) have become an important tool for remotely sensing water vapor in the atmosphere. In GNSS data processing, mapping functions and gradient models are needed to map the zenith tropospheric delay (ZTD) to the slant total tropospheric delay (STD) along a signal path. Therefore, it is essential to investigate the spatial–temporal performance of various mapping functions and gradient models in the determination of STD. In this study, the STDs at nine elevations were first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Our results show similar error levels for the VMF1 mapping function and similar unmodeled seasonal signatures when compared to results from similar assessment studies of Niell Mapping Function (NMF), Global Mapping Function (GMF), and VMF mapping functions [20][21][22][23]. Unlike the significant leap seen between the NMF and the VMF1 mapping functions, however, there is no significant advantage to switch from the VMF1 to the VMF3 mapping functions, even though VMF3 adopts a more accurate atmosphere data source and fitting strategy.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Our results show similar error levels for the VMF1 mapping function and similar unmodeled seasonal signatures when compared to results from similar assessment studies of Niell Mapping Function (NMF), Global Mapping Function (GMF), and VMF mapping functions [20][21][22][23]. Unlike the significant leap seen between the NMF and the VMF1 mapping functions, however, there is no significant advantage to switch from the VMF1 to the VMF3 mapping functions, even though VMF3 adopts a more accurate atmosphere data source and fitting strategy.…”
Section: Discussionsupporting
confidence: 70%
“…Similar studies have been done to assess the accuracy of other mapping functions by comparison with ray-tracing results [20][21][22][23]. Qiu et al [23] showed that VMF1 corresponds to the ERA-I numerical weather model better than the Niell Mapping Function [24] and the Global Mapping Function [25] at low elevation angles. Other studies rely on positioning or baseline length accuracies [16,26].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…where denotes the geopotential, and is a constant gravity value of 9.80665 m/s 2 . Second, ℎ was converted to the geometric height ℎ as follows [27,28]:…”
Section: B Conversion Of Height Systemmentioning
confidence: 99%
“…In regards to the mapping function, both the Neill mapping function (NMF) and global mapping function (GMF) [47,48] are available. As suggested by previous studies, although the Vienna mapping functions (VMF) have a better performance than the others, the difference among these commonly used mapping functions is quite small [49]. The gradient model parameters for the north and east are estimated together with the ZTD with the form proposed by Macmillan [50].…”
Section: Ztd Calculation With Gnssmentioning
confidence: 99%